Psychological distress and coping following eye removal surgery. (3rd May 2020) - Sadiq, S. A.; Pattinson, R.; Poole, H. M.; Bundy, C.
ABSTRACT: Purpose : Psychological distress is reasonably well documented in people with facial disfigurement; however, in patients following eye removal surgery this has not been studied adequately. We hypothesised that lower distress levels would be associated with age and more adaptive coping strategies and that women would be more likely to report higher levels of distress and, therefore, use maladaptive coping strategies. Methods : This exploratory, cross-sectional study measured distress and coping in a sample of 56 post enucleation or evisceration patients. The Hospital Anxiety and Depression Scale and the Brief COPE measured distress and coping strategies. Results : In all, 25.5% and 10.9% of the sample had high levels of anxiety and depression, respectively. Significant associations were found between levels of distress, coping strategies and demographic variables ( p < .05). There were significant differences in coping strategies between those with higher and lower levels of distress ( p < .05). Females reported higher levels of anxiety ( U = 202.5, p < .01) and depression ( U = 229, p < .05) than males. Those who experienced enucleation or evisceration aged between 20 and 39 years reported significantly higher levels of depression compared with other age groups ( U = 68.5, p < .01). Conclusions : There was a relatively low level of distress across the whole sample, but we found high levels of distress in a considerable proportion (18.18%) of participants. Participants' coping strategies and levels of distress were correlated. Females and participants aged between 20 and 39 years at time of eye removal were particularly vulnerable to distress.